2016
DOI: 10.1182/blood-2016-02-699843
|View full text |Cite
|
Sign up to set email alerts
|

Candidate driver genes involved in genome maintenance and DNA repair in Sézary syndrome

Abstract: Key Points Aberrations in genome maintenance and DNA repair genes including POT1 occur at a high frequency in Sézary syndrome. Candidate driver genes and affected pathways in Sézary syndrome show extensive heterogeneity but overlap with other mature T-cell lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 89 publications
4
101
1
Order By: Relevance
“…Therefore, we cannot conclude that HAT inactive-mutation is a general major cause of HDAC activation in CTCL. Another possibility is that there may be a critical novel cascade that regulates HDACs downstream of these oncogenic products, because there are several active mutations of the oncogenic transcription factors in CTCL [39]. Indeed, it has been demonstrated that the Myc transcription factor, which is frequently dysregulated in almost all advanced cancers, has the potential to recruit HDAC3 in mantle cell lymphoma [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot conclude that HAT inactive-mutation is a general major cause of HDAC activation in CTCL. Another possibility is that there may be a critical novel cascade that regulates HDACs downstream of these oncogenic products, because there are several active mutations of the oncogenic transcription factors in CTCL [39]. Indeed, it has been demonstrated that the Myc transcription factor, which is frequently dysregulated in almost all advanced cancers, has the potential to recruit HDAC3 in mantle cell lymphoma [40].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, a strong correlation was found between p53 functional status and clinical outcomes in lymphoma, such as mortality or resistance to chemotherapy (8, 9). TP53 may be mutated in a proportion of patients with another type of CTCL, Sezary syndrome, but mutations are not predictive for the course of the disease (10). Less is known about TP53 gene status in MF.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] These studies have now confirmed, expanded, and functionally validated many of the genetic aberrations detected by aCGH in MF/SS, a broad and diverse spectrum that include genes associated with T-cell receptor (TCR) signaling, activation of NF-kB, JAK/STAT signaling, chromatin remodeling, and DNA damage response. However, despite a significant degree of overlap, there was great variability in the identity and frequency of alterations at putative driver genes across studies.…”
mentioning
confidence: 72%